Entrapment history of aqueous fluids in Archean cherts from the Barberton Greenstone Belt, South Africa - Deutschmann, Christoph; Hopp, Jens; Trieloff, Mario; Ott, Uli (Precambrian research, 2022)
We performed fluid inclusion microthermometric analyses of four cherts and one silicified anhydrite from various successions of the Mesoarchean Barberton Greenstone Belt, South Africa, and constrained the entrapment conditions and provenance of fluids that were incorporated during different magmatic or tectono-thermal events. Major saline aqueous fluid inclusion assemblages in cherts from the 3.2 Ga old Mendon Formation (Barite Valley Syncline, Power Line Road) and from the 3.42-3.45 Ga old uppermost Hooggenoeg Formation (Buck Reef Chert) correspond to fluids incorporated during metamorphism. Their documented P-T conditions compare well with reported petrologic constraints. In Buck Reef chert we also found a distinctive suite of inclusions with high salinities and low homogenization temperatures (61-118 °C). This is in agreement with a hydrothermal formation of these fluids at subseafloor conditions. Finally, we investigated quartz in a silicified anhydrite and its sandstone host from the Stolzburg Syncline (Moodies Group, ca. 3.2 Ga). One major inclusion assemblage in the evaporite and in adjacent quartz within the embedding sandstone share the P-T range observed for the cherts from the Mendon Fm. Its incorporation is postdating the silicification process. We also found two higher temperature inclusion types that favor a magmatic origin. In particular, one of these inclusion suites is only observed in quartz within the matrix and likely mirrors trapping of brines associated with magmatic fluids predating sedimentation of the sandstone, e.g., from the potential magmatic source region of the quartz. Our results indicate the presence of coexisting aqueous fluids in cherts derived from distinct source environments, spanning an age range of several 100 Ma on a grain scale. The earliest hydrothermal aqueous inclusions were documented in a Buck Reef chert (3.42-3.45 Ga), whereas the majority of aqueous fluids are metamorphic in origin and likely related to the documented 3.23 Ga and 3.1 Ga tectono-thermal events. Our findings demonstrate that constraining environmental conditions by the volatile record of Archean cherts requires analyses on inclusion, not grain scale.
Available online 7 December 2021
Gesehen am 23.05.2022